(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Inguinal hernia repair is among the most frequently executed operations in general surgery. The Lichtenstein tension-free open mesh hernioplasty is the predominant standard procedure, recognized for its simplicity and minimal recurrence rates. Laparoscopic hernia surgery has become increasingly popular due to less postoperative pain, expedited recovery, and enhanced aesthetic outcomes. Despite these benefits, discrepancies in surgical duration, complications, and resumption of normal activities necessitate additional assessment. Aims: To compare postoperative outcomes of Lichtenstein’s open hernioplasty and laparoscopic hernioplasty in patients with inguinal hernias. Materials and Methods: This prospective comparative study was conducted in the Department of General Surgery over 15 months and included 70 patients with primary unilateral inguinal hernia. Patients were allocated into two equal groups of 35: Group A underwent Lichtenstein open mesh hernioplasty, and Group B underwent laparoscopic hernioplasty (TAPP/TEP). Inclusion criteria were adults aged 18–70 years with a primary unilateral inguinal hernia. Clinical evaluation, routine investigations, and preoperative assessment were performed for all patients. Operative time, intraoperative events, postoperative pain, analgesic requirement, complications, duration of hospital stay, and time to return to routine activities were recorded. Patients were followed up at one week, one month, three months, and six months to assess wound healing, chronic groin pain, and early recurrence. Results: The mean operative period was markedly extended in the laparoscopic group relative to the open group. Postoperative pain scores at 24 and 48 hours were markedly lower in Group B, and the requirement for analgesics was diminished. The occurrence of wound-related problems was elevated in Group A, while seroma development was marginally more prevalent in Group B, though not statistically significant. Patients who received laparoscopic surgery experienced a reduced hospital stay and resumed normal daily activities more swiftly than those who underwent open repair. The laparoscopic group exhibited greater cosmetic satisfaction. No significant problems were observed in either group. At the six-month follow-up, no recurrences were seen in either group. Conclusion: Lichtenstein’s open hernioplasty and laparoscopic hernioplasty are both efficacious methods for the correction of inguinal hernias. Laparoscopic repair has distinct benefits, including less postoperative pain, abbreviated hospital stay, and expedited resumption of normal activities, albeit necessitating a greater surgical duration.